Axonal GABAA stabilizes excitability in unmyelinated sensory axons secondary to NKCC1 activity - Bonalume, Veronica; Caffino, Lucia; Castelnovo, Luca F.; Faroni, Alessandro; Liu, Sheng; Hu, Jing; Milanese, Marco; Bonanno, Giambattista; Sohns, Kyra; Hoffmann, Tal; De Col, Roberto; Schmelz, Martin; et al. (The journal of physiology, 2021)
Key points GABA depolarized sural nerve axons and increased the electrical excitability of C-fibres via GABAA receptor. Axonal excitability responses to GABA increased monotonically with the rate of action potential firing. Action potential activity in unmyelinated C-fibres is coupled to Na-K-Cl cotransporter type 1 (NKCC1) loading of axonal chloride. Activation of axonal GABAA receptor stabilized C-fibre excitability during prolonged low frequency (2.5 Hz) firing. NKCC1 maintains intra-axonal chloride to provide feed-forward stabilization of C-fibre excitability and thus support sustained firing. Abstract GABAA receptor (GABAAR)-mediated depolarization of dorsal root ganglia (DRG) axonal projections in the spinal dorsal horn is implicated in pre-synaptic inhibition. Inhibition, in this case, is predicated on an elevated intra-axonal chloride concentration and a depolarizing GABA response. In the present study, we report that the peripheral axons of DRG neurons are also depolarized by GABA and this results in an increase in the electrical excitability of unmyelinated C-fibre axons. GABAAR agonists increased axonal excitability, whereas GABA excitability responses were blocked by GABAAR antagonists and were absent in mice lacking the GABAAR β3 subunit selectively in DRG neurons (AdvillinCre or snsCre). Under control conditions, excitability responses to GABA became larger at higher rates of electrical stimulation (0.5-2.5 Hz). However, during Na-K-Cl cotransporter type 1 (NKCC1) blockade, the electrical stimulation rate did not affect GABA response size, suggesting that NKCC1 regulation of axonal chloride is coupled to action potential firing. To examine this, activity-dependent conduction velocity slowing (activity-dependent slowing; ADS) was used to quantify C-fibre excitability loss during a 2.5 Hz challenge. ADS was reduced by GABAAR agonists and exacerbated by either GABAAR antagonists, β3 deletion or NKCC1 blockade. This illustrates that activation of GABAAR stabilizes C-fibre excitability during sustained firing. We posit that NKCC1 acts in a feed-forward manner to maintain an elevated intra-axonal chloride in C-fibres during ongoing firing. The resulting chloride gradient can be utilized by GABAAR to stabilize axonal excitability. The data imply that therapeutic strategies targeting axonal chloride regulation at peripheral loci of pain and itch may curtail aberrant firing in C-fibres.
First published: 26 June 2021
Gesehen am 11.01.2023